«Մասիս» գրական շաբաթաթերթ (1900–1908) - Խառատյան, Ալբերտ (Զանգակ հրատ.)
In 1900– 1908 “Masis” appeared as a literary weekly being one of the best Armenian publications in the field. Thanks to editors T. Arpiaryan and A. Enovqn, western Armenian representatives of literary and literary criticism genre (e.g., Gr. Zohrap, M. Metsarents, R. Sevak, Art. Harutyunyan, Z. Esayan, A. Antonyan, E. Temirchipashyan, H. Alpiar, T. Chyokuryan and others) united around “Masis” promoting the development of Armenian literature. “Masis” brought forward its vision and preferences introducing its readers not only to the national artistic values but also to other nations’ literary and aesthetic movements (e.g., realism, romanticism, symbolism, decadence, etc.) In its publications about the development of the national literature, the weekly paper aimed at difference in length of sight through the reflection of general outlook of the state–of–the–art literary and aesthetic perceptions. В 1900–1908 гг. «Масис» издавался в качестве литературного еженедельника и считался популярным и наилучшим армянским изданием ного времени. Благодаря редакторам Т. Арпиаряну и Енокву. Армену вокруг «Масиса» сплотились лучшие умы западноармянской литературно–критической мысли (таких, как Гр. Зохрап, М. Мецаренц, П. Севак, А. Арутюнян, З. Есаян, А. Антонян, Е. Темирчипашян, Г. Алпиар, Т. Чёкюрян и другие), тем самым способствуя развитию армянской литературы. Основной целью выхода в свет еженедельника являлось не только ознакомление читателя с национальными традиционными литературными ценностями, а также формирование представлений о научном и литературном достижении других национальностей (реализм, романтизм, символизм, декаданс и др.). В своих изданиях еженедельник стремился к достижению плюрализма мнений относительно развития национальной литературы, тем самым отображая общую картину литературно–художественных и эстетических представлений времени.
Keywords: Գիտնականի մտորումներ; Հայ պարբերական մամուլ